Activation patterns in back and shoulder girdle muscles in recurve archers - Kolayis, I. E.; Ertan, H.; Kolayis, H. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume II: Bio-Mechanics and Sports Engineering., 2008)
The purpose of this study was to investigate the activation patterns of shoulder girdle and glenohumeral joint muscles during archery shooting. The eight subjects that have been involved in the current study were the associate archers for Turkish junior national team (age 16,38±0,86; years of training 1,94±1,04; FITA scores 1083,75±71,02). The measurement sites were prepared according to SENlAM's recommendations. Pass band of EMG amplifier, sampling rate, maximum intra-electrode impedance and common mode rejection ratio (CMMR) were 8-500 Hz, 1000 Hz, 6 kOhms and 95 dB, respectively. The archers engaged in a single test session consisting of 15 shots, the first three being trial shots. EMG activities of M. Deltoid Middle (DM), M. Deltoid Posterior (DP). M. Trapezius Middle(TM). and M. Trapezius Lower (TL) were quantified in both drawing arm and in bow arm. Three-second periods of twelve shots' EMG data were full-wave rectified and filtered (moving average filter with 60 ms time-window) for each archer. The resulls of the study are drawing arm DM, DP, TM and muscles has exhibited gradually increasing slop till the clicker released and then rapid inclination, drawing arm TL muscle has not seemed so active, its MVC% was changed 10-12% till the clicker released and then has fall down 5%. Bow arm DM and TM muscles has showed gradually increasing slop before clicker released and then there were an rapid inclinalion, DP and TL showed stable slop in 22-25%, 15% respectively.